Validade e reprodutibilidade de questionário de atividade física do sistema de vigilância de fatores de risco e proteção para doenças crônicas por inquérito telefônico - Alexandra Dias Moreira (2013)
Introduction: The telephone-based risk factor surveillance system for chronic diseases (VIGITEL) aims to monitor the frequency of risk factors and chronic diseases in Brazil. Physical activity is one of the most important resources in avoiding health impairments and it is assessed, among other approaches, in VIGITEL questionnaire. Objective: To evaluate the reliability and concurrent validity of physical activity indicators in a telephone-based surveillance system in Belo Horizonte, Minas Gerais. Methods: The reliability of the physical activity indicators was assessed through repeated VIGITEL interviews with intervals of 7-15 days obtained from 305 individuals in Belo Horizonte, 2013, that responded to the original surveillance system. The evaluated indicators included physical activity on leisure time, physical activity in transportation, inactive in four domains of physical activity (leisure, work, transportation and housework) and watching television for long periods habit. Kappa coefficient was used to measure agreement between both interviews. For the concurrent validity assessment, the same subjects that participated in the reliability study also responded to the Global Physical Activity Questionnaire (GPAQ), an international validated questionnaire used as reference method for comparison of VIGITEL physical activity indicators. Watching television for long periods wasnt compared because GPAQ doesnt present this information. Comparison was assessed by measures of sensitivity, specificity, positive and negative predictive values (PPV and NPV). Results: The reliability study showed substantial agreement between repeated interviews for frequency of active individuals in leisure time and inactive in four domains of physical activity, kappa statistics 0.70 and 0.64 respectively. The indicator related to long periods of television watching was classified as moderate agreement and the frequency of individuals active in transportation showed a kappa index of 0.35, indicating fair agreement. The comparison analyses to the reference method ranged from 54.8 to 67.7 of sensitivity in frequency of inactive in four domains of physical activity, active in leisure time and work. The domain of transportation was represented only by 11.9 of sensitivity. Specificity ranged from 72.0 to 91.2 in four domains of physical activity and inactive indicator. PPV and NPV showed large variability (PPV: 34.0 to 86.2; NPV: 49.6 to 94.4). Conclusion: The VIGITEL physical activity questionnaire seems to be reliable in all domains, except in questions related to transportation. In this sense, VIGITEL was considered comparable to GPAQ in most variables, as presented in concurrent validity.